Evaluation of Blood Pressure Changes Using Ambulatory Blood Pressure Monitoring (ABPM) in Children Undergoing Kidney Transplantation and its Relationship with Left Ventricular Mass Index, and Level of Serum Angiotensin and Atrial Natriuretic Peptide - Alaleh Gheisari; Mohammad Reza Sabri; Hamid Reza Pirpiran; Shaghayegh Haghjooy Javanmard (مجله دانشکده پزشکی اصفهان, 2012)
Background: Hypertension is a problem in patients undergoing kidney transplantation. This problem can affect renal functioning, and increase heart failure and death in these patients. This study aimed to determine changes in blood pressure using ambulatory blood pressure monitoring (ABPM) in children undergoing kidney transplantation and its relationship with left ventricular mass index, and level of serum angiotensin and atrial natriuretic peptide. Methods: In the present descriptive study 35 patients, who were undergoing kidney transplantation and under 18 years of age, underwent examination and measurement of blood pressure using the mercury barometer and ABPM methods within 24 hours. For each patient, cardiac left ventricular mass index using echocardiogram, and level of serum angiotensin and atrial natriuretic peptide were measured. Findings: Results showed that serum angiotensin level and index of average diastolic blood pressure during the day had a reverse correlation and significant difference. Moreover, serum angiotensin level, and nocturnal systolic and diastolic hypotension had a significant difference and a direct correlation. Furthermore, systolic blood pressure at rest during the day and diastolic blood pressure during the night using 24-hour ABPM compared with a mercury barometer was significantly different. However, no correlation with the other indices was observed. The average left ventricular mass index and serum and atrial natriuretic peptide had no significant correlation with systolic and diastolic blood pressure, heart rate during the day and night, and average diastolic and systolic hypotension during the night. Conclusion: Due to registration of changes, ABPM method can be more effective in controling of blood pressure changes within 24 hours. Serum angiotensin level has a reverse correlation with average diastolic blood pressure during the day, but has a direct correlation with nocturnal systolic and diastolic hypotension.